Tumors and pseudotumors at the temporomandibular joint region in pediatric patients - Wei, Wen-Bin (Int J Clin Exp Med, 2015)
Objective: To describe the clinical manifestations and types of, and our surgical experience with, neoplasms in the region of the temporomandibular joint (TMJ) in pediatric patients. Materials and Methods: From September 1997 to December 2013, a total of 18 patients with neoplasms in the region of the TMJ were treated at our department. They all underwent open surgeries. The clinical manifestations and radiological aspects of all the patients were reviewed. The average follow-up period was 61.8 months with a range of 12-221 months. We reviewed the history, physical examination, images, and related radiological examinations. Results: Of the 18 patients, 14 had benign tumors or pseudotumors, and four had malignant tumors. The ratio of pseudotumor to benign tumor to malignant tumor was 2.5:1:1. Limitations of mouth opening were more likely to occur with malignant tumors, and facial deformity had a higher incidence in benign tumors. Local resection was the first choice for patients with benign tumors or pseudotumors. All patients with malignant tumors underwent whole-tumor resection along the boundary, including the joint capsule, disc, and part of the temporal bone and mandible. During the follow-up period, no tumor reformation or new deformity was detected. Conclusions: In the diagnosis of masses in the TMJ region, CT and MRI play an important role. Surgical removal of the mass with/without joint attachment was sufficient to treat benign and malignant tumors.